Integration of safety aspects in the maintenance work of a living wall: an overview of practice and challenges / Loo Jun Han and Nazirah Zainul Abidin - Loo, Jun Han; Zainul Abidin, Nazirah (UiTM Press, 2021)
Building maintenance is crucial to prolong a building's lifespan. Conducting the maintenance work can be dangerous, especially if it involves high-rise areas such as walls and roofs. Most literature discusses safety aspects at the construction site, while the safety aspects of maintenance work, which occur after occupancy, received less attention. This paper discusses the potential of integrating safety aspects into the maintenance work of a living wall. Living wall system (LWS) is one of the green design aspects in which the wall is designed to allow for vegetation growth. Maintenance works of a living wall involve various risks especially working in high or difficult places. This paper reviews the maintenance process and techniques adapted for maintaining the living wall through literature. This paper presents the safety practices that have the potential to reduce the risks of conducting maintenance work on the living wall and its potential challenges. It is hoped that this paper raises further awareness that work safety in construction is not only enclosed within the construction site and its vicinity, but safety should also be considered post-occupation, especially when the design demands specific maintenance requirements such as a living wall.